A decomposable freight wagon frame suitable for bimodal transport systems that uses a fast locking mechanism. (May 2014) - De Iorio, Antonio; Grasso, Marzio; Penta, Francesco; Pucillo, Giovanni Pio; Chioccola, Francesco
This paper describes a novel connection system which allows fast, safe and reliable coupling and uncoupling of two sections of a freight wagon body as part of a bimodal transport system. The connection system allows the time for loading and unloading a truck trailer to be reduced to almost one-half of the current duration. The connection system is composed of a cylindrical clamping pin with three conical shoulders at one end and an axial slide. A crank mechanism in a cylindrical guide is used to lock the clamp. The crank is connected to the pin and symmetric piston rods are connected to the moving clamp, other auxiliary members constrain the clamp.